MAN'S RELATIONSHIP WITH NATURE IN THE TAFSIR AL-IBRIZ AND AL-MISHBAH - Ali Abdur Rohman; Moh. Wafiq Faulal Ahsan (IAIN Tulungagung, 2022)
This study aims to compare the interpretations of Al-Ibriz and Al-Mishab in relation to the relationship between humans and nature. The formulation of the problem raised by the author is: